2018
DOI: 10.5194/angeo-36-301-2018
|View full text |Cite
|
Sign up to set email alerts
|

Mesopause region temperature variability and its trend in southern Brazil

Abstract: Abstract. Nowadays, the study of the upper atmosphere is increasing, mostly because of the need to understand the patterns of Earth's atmosphere. Since studies on global warming have become very important for the development of new technologies, understanding all regions of the atmosphere becomes an unavoidable task. In this paper, we aim to analyze the temperature variability and its trend in the mesosphere and lower thermosphere (MLT) region during a period of 12 years (from 2003 to 2014). For this purpose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Despite the short period of data considered here, the results for Cachoeira Paulista are qualitatively consistent with those of Huang et al () that, using data from SABER instrument obtained between 2002 and 2014, have found a positive temperature response at 80‐ to 100‐km height to solar variability for 48°N to 48°S latitude range, but the period of 13 years is not long enough to establish reliable trends. Venturini et al () have used SABER temperature to investigate MLT temperature variability and its trend in Brazilian southern (29.7°S) and founded a positive trend of 0.58 K per decade at 85 km, a negative trend of 0.02 K per decade at 90 km, and another positive trend of 0.41 K per decade at 95 km, from 2003 to 2014 (12 years), concluding that there is no variability tendency in MLT temperature. The authors also have noted that during years of maximum solar the temperature's amplitude is twice the amplitude of the year of solar minimum, deducing that amplitudes of annual and semiannual variation are directly influenced by the solar cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the short period of data considered here, the results for Cachoeira Paulista are qualitatively consistent with those of Huang et al () that, using data from SABER instrument obtained between 2002 and 2014, have found a positive temperature response at 80‐ to 100‐km height to solar variability for 48°N to 48°S latitude range, but the period of 13 years is not long enough to establish reliable trends. Venturini et al () have used SABER temperature to investigate MLT temperature variability and its trend in Brazilian southern (29.7°S) and founded a positive trend of 0.58 K per decade at 85 km, a negative trend of 0.02 K per decade at 90 km, and another positive trend of 0.41 K per decade at 95 km, from 2003 to 2014 (12 years), concluding that there is no variability tendency in MLT temperature. The authors also have noted that during years of maximum solar the temperature's amplitude is twice the amplitude of the year of solar minimum, deducing that amplitudes of annual and semiannual variation are directly influenced by the solar cycle.…”
Section: Discussionmentioning
confidence: 99%
“…[56,57] Among all the zeolites that are used contemporarily for industrial purposes, zeolite Y (faujasite, FAU) has been one of the most extensively used materials. [58][59][60] Hydrothermal synthesis is the primary method for preparing zeolite Y. It is a natural process which efficiently produces various classes of minerals such as crystalline silica and zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…The practical use of hydrated ethanol represents an essential factor for the reducing costs related to the energy consumed in the process (Venturini et al, 2018;Tura et al, 2018;Matugi et al, 2018;Robertson and Pavlath, 1985;Fagundez et al, 2017;Cataluña et al, 2017). The production of first and second-generation ethanol in the same industrial plant presents better financial results compared to the isolated processes (Silva et al, 2017;Caetano et al, 2015b;Dias et al, 2012;Ojeda et al, 2011;Seabra et al, 2010).…”
Section: Introductionmentioning
confidence: 99%